PENGARUH PENDIDIKAN KESEHATAN TERHADAP DISPAREUNIA PADA PEREMPUAN MENOPAUSE - Lisda Maria; RATNA SARI (Jurnal Kesehatan dan Pembangunan, 2023)
Background: Menopausal women experience symptoms of menopause almost all over the world, around 70-80% of European women 60%. In America 57% in Malaysia 18% in China and 10% in Japan and Indonesia. From some data it appears that one of the factors of the difference in numbers is due to diet. European and American women have more estrogen than Asia. The decrease in estrogen levels causes symptoms that greatly interfere with the activities of women's lives. The purpose of the study was to determine the effect of health education on dyspareunia in postmenopausal women at Kayu Agung Hospital in 2022. The research method used a pre-experimental research design with a pretest-posttest approach without control. The research sample amounted to 40 people. The results of the study, most of the respondents experienced dyspareunia in category two, namely 42.5%, then in category one, namely 37.5%, the remaining dyspareunia scores in category three, namely 20.0%, it was found that there was an effect of health education on dyspareunia in postmenopausal women at RSUD Kayu Agung in 2022 with p value = 0.000. It is recommended to develop a health education system research for postmenopausal women, especially those experiencing dyspareunia so that mothers have the knowledge to overcome the symptoms of dyspareunia.